2006
DOI: 10.4049/jimmunol.177.7.4644
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Recall Responses Mediated by CD8 T cells during Intracellular Bacterial Challenge Infection

Abstract: The roles(s) of CD8 T cells during infections by intracellular bacteria that reside in host cell endocytic compartments are not well understood. Our previous studies in a mouse model of human monocytotropic ehrlichiosis indicated that CD8 T cells are not essential for immunity. However, we have observed an unexpected role for these cells during challenge infection. Although immunocompetent mice cleared a primary low-dose (nonfatal) Ixodes ovatus ehrlichia infection, a secondary low-dose challenge infection res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
1
20
1
1
Order By: Relevance
“…In contrast, substantial expansion of pathogenic TNF-␣-producing CD8 ϩ T cells in fatal primary ehrlichial infection coincides with a simultaneous decline in the total number of CD4 ϩ T cells due to apoptotic cell death that results also in a weak CD4 ϩ Th1 response (11,12). Although a previous study by Bitsaktsis et al suggested that fatal recall response is mediated by pathogenic memory CD8 ϩ T cells, our current model of fatal secondary ehrlichiosis is different from their study (3). The study by Bitsaktsis et al showed that fatal recall response is associated with high bacterial burden and pathology identical to primary high-dose IOE infection (3).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In contrast, substantial expansion of pathogenic TNF-␣-producing CD8 ϩ T cells in fatal primary ehrlichial infection coincides with a simultaneous decline in the total number of CD4 ϩ T cells due to apoptotic cell death that results also in a weak CD4 ϩ Th1 response (11,12). Although a previous study by Bitsaktsis et al suggested that fatal recall response is mediated by pathogenic memory CD8 ϩ T cells, our current model of fatal secondary ehrlichiosis is different from their study (3). The study by Bitsaktsis et al showed that fatal recall response is associated with high bacterial burden and pathology identical to primary high-dose IOE infection (3).…”
Section: Discussioncontrasting
confidence: 46%
“…Previous studies suggest that TNF-␣ plays an important role in the pathogenesis of fatal primary and secondary ehrlichiosis (3,12,13). However, splenocytes cultured from E. murisprimed mice produce high levels of proinflammatory TNF-␣ in vitro compared to those of IOE-primed mice on day 28 after primary infection and on day 7 after secondary IOE challenge (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that immune-mediated pathology plays a role in IOEinduced disease and that protective immunity against IOE reinfection in E. muris-primed mice involves at least two components: (i) the protective mechanisms that prevent bacterial replication and eliminate IOE and (ii) the regulatory mechanisms that prevent IOE-induced immune-mediated pathology. Overproduction of tumor necrosis factor alpha by antigenspecific CD8 ϩ T cells and effector/memory CD8 ϩ T cells is implicated in IOE-induced immune-mediated pathology during primary and secondary IOE infections, respectively (6,17).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant IOE OMP-19 was used to immunize mice subcutaneously in the presence of CFA. The mice were challenged at least 30 days later with 2ϫ LD 50 of IOE (approximately 500 bacteria [3]). Mice immunized with IOE OMP-19/CFA, but not CFA alone, were protected from IOE challenge (Fig.…”
Section: Recombinant Omps Mediate Protection Against Fatal Ioe Infectmentioning
confidence: 99%